On Types of Solutions of the Second Order Nonlinear Boundary Value Problems - Maria Dobkevich; Felix Sadyrbaev; Nadezhda Sveikate; Inara Yermachenko (Abstract and Applied Analysis)
We review the results concerning types of solutions of boundary value problems for the second order nonlinear equation (l2x)(t)=f(t,x,x′), where (l2x)(t) is the second order linear differential form. The existence results and the multiplicity results are stated in terms of types of solutions.